Correction: Wind conditions do not consistently affect large-scale movement decisions of large savanna herbivores - Sara Gomez; Melinda Boyers; Alexandre Caron; Daniel Cornelis; Henjo de Knegt; Michel de Garine-Wichatitsky; Jasper A. J. Eikelboom; J. Werner Kilian; Norman Owen-Smith; Thomas Prin; Adrian M. Shrader; Jared A. Stabach; et al. (Oecologia, 2026)

Wind conditions do not consistently affect large-scale movement decisions of large savanna herbivores - Sara Gomez; Melinda Boyers; Alexandre Caron; Daniel Cornelis; Henjo de Knegt; Michel de Garine-Wichatitsky; Jasper A. J. Eikelboom; J. Werner Kilian; Norman Owen-Smith; Thomas Prin; Adrian M. Shrader; Jared A. Stabach; et al. (Oecologia, 2026)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Corrigendum to “Spatial mechanistic modelling to simulate movements and contacts between wildlife and livestock in Southern Africa” [ecological modelling 498 (2024) /110863] - Florent Rumiano; Eve Miguel; Victor Dufleit; Pascal Degenne; Cedric Gaucherel; Hugo Valls-Fox; Michel de Garine-Wichatitsky; Edson Gandiwa; Alexandre Caron; Annelise Tran (Ecological Modelling, 2024)

Spatial mechanistic modelling to simulate movements and contacts between wildlife and livestock in Southern Africa - Florent Rumiano; Eve Miguel; Victor Dufleit; Pascal Degenne; Cédric Gaucherel; Hugo Valls-Fox; Michel de Garine-Wichatitsky; Edson Gandiwa; Alexandre Caron; Annelise Tran (Ecological Modelling, 2024)

The evolution of latitudinal ranges in reef‐associated fishes: Heritability, limits and inverse Rapoport's rule - Marcio R. Pie; Raquel Divieso; Fernanda S. Caron; Alexandre C. Siqueira; Diego R. Barneche; Osmar J. Luiz (Journal of Biogeography, 2021)
Aim Variation in the size and position of geographical ranges is a key variable that underlies most biogeographical patterns. However, relatively little is known in terms of general principles driving their evolution, particularly in the marine realm. In this study we explore several fundamental properties regarding the evolution of reef fish latitudinal ranges, namely the degree of similarity in range size between ancestor and descendant lineages (i.e. phylogenetic signal); the evolution of range limits; and the latitudinal distribution of range sizes, particularly with respect to Rapoport's rule. Location Global. Taxon Reef‐associated fishes. Methods We integrate data on the latitudinal distribution and evolutionary history of 5,071 reef fish species with phylogenetic comparative methods to assess the level of phylogenetic signal in latitudinal range size, low‐ and high‐latitude limits and range midpoints, and to estimate rates of evolution of those traits. Finally, we test whether latitudinal ranges become smaller near the equator, as predicted by Rapoport's rule, using phylogenetic generalized least squares. Results There were varying levels of phylogenetic signal in latitudinal range size, low‐ and high‐latitude limits and range midpoints. Despite these differences, latitudinal midpoints were consistently shown to have the highest phylogenetic signal among all measured geographical features. Interestingly, the position of high‐latitude limits in general evolved at substantially faster rates than their low‐latitude counterparts. Finally, we confirm for the first time the existence of an inverse Rapoport's rule in reef‐associated fishes using phylogenetic comparative methods. Indeed, mean latitudinal range size of tropical species is nearly twice the size of their temperate counterparts (2,067 ± 1,431 km vs. 1,168 ± 725 km respectively). Main conclusions We uncovered several congruent patterns in phylogenetic signal and rates of evolution of latitudinal ranges, despite vastly disparate biogeographical distributions and ecological differences between the studied fish lineages. Such broad congruence across different taxa and oceans, as well as with previous data from terrestrial environments, suggests that the observed patterns might represent general principles governing geographical range evolution.

Nuclear and plastid SNP markers for tracing Cedrela timber in the tropics - Kathelyn Paredes-Villanueva; Celine Blanc-Jolivet; Malte Mader; Eurídice N. Honorio Coronado; Carmen Garcia-Davila; Alexandre M. Sebbenn; Barbara Rocha Venancio Meyer-Sand; Henri Caron; Niklas Tysklind; Stephen Cavers; Bernd Degen (Conservation Genetics Resources, 2020)

Development of nuclear and plastid SNP and INDEL markers for population genetic studies and timber traceability of Carapa species - Niklas Tysklind; Céline Blanc-Jolivet; Malte Mader; Barbara R. V. Meyer-Sand; Kathelyn Paredes-Villanueva; Eurídice N. Honorio Coronado; Carmen R. García-Dávila; Alexandre M. Sebbenn; Henri Caron; Valerie Troispoux; Erwan Guichoux; Bernd Degen (Conservation Genetics Resources, 2019)

Survey of brucellosis at the wildlife–livestock interface on the Zimbabwean side of the Great Limpopo Transfrontier Conservation Area - Calvin Gomo; Michel de Garine-Wichatitsky; Alexandre Caron; Davies Mubika Pfukenyi (Tropical Animal Health and Production, 2012)

Characterization of Bovine Adenovirus Type 3 Early Region 2B - Mohit K. Baxi; P. Seshidhar Reddy; Alexandre N. Zakhartchouk; Neeraja Idamakanti; Caron Pyne; Lorne A. Babiuk; Suresh K. Tikoo (Virus Genes, 1998)